1997
DOI: 10.1152/ajpcell.1997.273.3.c1082
|View full text |Cite
|
Sign up to set email alerts
|

Effects of epinephrine on insulin-stimulated glucose uptake and GLUT-4 phosphorylation in muscle

Abstract: beta-Adrenergic stimulation has been reported to inhibit insulin-stimulated glucose transport in adipocytes. This effect has been attributed to a decrease in the intrinsic activity of the GLUT-4 isoform of the glucose transporter that is mediated by phosphorylation of GLUT-4. Early studies showed no inhibition of insulin-stimulated glucose transport by epinephrine in skeletal muscle. The purpose of this study was to determine the effect of epinephrine on GLUT-4 phosphorylation, and reevaluate the effect of bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
52
2
1

Year Published

2001
2001
2012
2012

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(57 citation statements)
references
References 22 publications
2
52
2
1
Order By: Relevance
“…Most likely PDE3B which is a membrane associated enzyme [3] regulates a cAMP pool different from a pool regulated by PDE4, an enzyme found mainly in the cytosolic fraction of adipocytes [28]. In a number of other cell types [44][45][46] and in several PDE3 and PDE4 knock out mice models [47][48][49] A correlation between cAMP-mediated inhibition of insulin-induced glucose uptake and inhibition of translocation of GLUT-4 to the plasma membrane has been shown in some studies [8] but not in others [6]. Isoproterenol-induced inhibition of insulin-induced glucose uptake in the presence of ADA was suggested to be caused by trapping of GLUT-4 in occluded vesicles associated with the plasma membrane during exocytosis, rather than by reduction of total plasma membrane GLUT-4 content [6].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Most likely PDE3B which is a membrane associated enzyme [3] regulates a cAMP pool different from a pool regulated by PDE4, an enzyme found mainly in the cytosolic fraction of adipocytes [28]. In a number of other cell types [44][45][46] and in several PDE3 and PDE4 knock out mice models [47][48][49] A correlation between cAMP-mediated inhibition of insulin-induced glucose uptake and inhibition of translocation of GLUT-4 to the plasma membrane has been shown in some studies [8] but not in others [6]. Isoproterenol-induced inhibition of insulin-induced glucose uptake in the presence of ADA was suggested to be caused by trapping of GLUT-4 in occluded vesicles associated with the plasma membrane during exocytosis, rather than by reduction of total plasma membrane GLUT-4 content [6].…”
Section: Discussionmentioning
confidence: 95%
“…However, different effects of these agents have been reported. Thus, cAMP-increasing β-adrenergic agonists have been shown to increase [6,7], to have no effect on [8,9], or to decrease [10][11][12] insulin-induced glucose uptake in adipocytes. Studies using PDE3 inhibitors, OPC3911 and cilostamide, showed impaired, [13,14] or unaffected [15] insulin-induced glucose uptake in adipocytes.…”
Section: Introductionmentioning
confidence: 99%
“…The administration of supra-physiological concentrations of adrenaline increases GLUT4 translocation and decreases 3-O-methyl glucose transport in perfused rat muscle, thus implying a decrease in GLUT4 intrinsic activity (Bonen et al 1992). In contrast, b-adrenergic stimulation does not directly inhibit insulin-stimulated (Lee et al 1997;Aslesen & Jensen, 1998) or contraction-stimulated (Aslesen & Jensen, 1998) glucose transport in vitro. Taken together, these findings suggest that adrenaline-mediated decreases in glucose uptake by skeletal muscle are likely to be due to a reduction in glucose phosphorylation and a subsequent inhibition of transport.…”
Section: Discussionmentioning
confidence: 98%
“…Studies conducted in vitro support such a mechanism (Chiasson et al 1981;Aslesen & Jensen, 1998). In contrast, most studies have observed that both insulin- (Lee et al 1997;Aslesen & Jensen, 1998) and contraction-(Aslesen & Jensen, 1998) stimulated glucose transport in vitro are unaffected by b-adrenergic stimulation, although this remains equivocal (Bonen et al 1992). Hence previous studies suggest a role for adrenaline in inhibiting glucose uptake via decreased glucose transport secondary to an inhibition of glucose phosphorylation.…”
mentioning
confidence: 97%
“…␤-Adrenergic action and cAMP have been implicated as negative regulators of insulin action (20,23,26,38,43). GS, the rate-limiting enzyme for the storage of intracellular glucose as glycogen in skeletal muscle (25), is activated in the presence of insulin and inhibited by agents that increase intracellular cAMP concentrations ([cAMP]) (7,25,38).…”
mentioning
confidence: 99%